2002
DOI: 10.2307/3061136
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Effects of Landscape Structure on Biological Control in Agroecosystems

Abstract: Habitat fragmentation may adversely affect the ability of natural enemies to control pest outbreaks in agricultural landscapes by interfering with their search behavior and ability to aggregate in response to prey. We determined how landscape structure affected the ability of two ladybird beetles (Coleoptera: Coccinellidae) to track aphid populations in experimental landscapes that differed in the abundance and degree of fragmentation of red clover (Trifolium pratense). One coccinellid was a native species (Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 37 publications
1
80
1
2
Order By: Relevance
“…Accordingly, the strength and direction of landscape quality effects on parasitism rates are contingent on parasitoid traits such as search behavior and dispersal ability (Bianchi, Ives, and Schellhorn 2013). This is complicated by the fact that the scale of these responses can greatly vary from species to species depending on their dispersal capabilities and even closely related species often lumped into the same functional group can perceive landscape fragmentation differently (Doak, Marino, and Kareiva 1992;Gardiner et al 2009b;With and Crist 1995;With et al 2002). For example, Kareiva and Odell (1987) found that since two ladybeetle species have different abilities to track patches of high prey density, habitat fragmentation had a different effect on each species.…”
Section: Local and Landscape Drivers Of Functional Traitsmentioning
confidence: 99%
“…Accordingly, the strength and direction of landscape quality effects on parasitism rates are contingent on parasitoid traits such as search behavior and dispersal ability (Bianchi, Ives, and Schellhorn 2013). This is complicated by the fact that the scale of these responses can greatly vary from species to species depending on their dispersal capabilities and even closely related species often lumped into the same functional group can perceive landscape fragmentation differently (Doak, Marino, and Kareiva 1992;Gardiner et al 2009b;With and Crist 1995;With et al 2002). For example, Kareiva and Odell (1987) found that since two ladybeetle species have different abilities to track patches of high prey density, habitat fragmentation had a different effect on each species.…”
Section: Local and Landscape Drivers Of Functional Traitsmentioning
confidence: 99%
“…Recently some scholars incorporated temporal changes in landscape structure (Solbreck, 1995;Onstad et al, 2001), genetic change in insect populations (Singer & Thomas, 1996;Ronce & Kirkpatrick, 2001), and differential responses of predators and prey (Kruess & Tscharntke, 1994;With et al, 2002) into their understanding of the spatial ecology of insects (Hunter, 2002). Roderick and Navajas (2003) suggested that identifying the origin of specific genotypes in an invasive pest population might assist in the identification of natural enemies in the native range, thus facilitating the design of effective biological control programs (Rollins et al, 2006).…”
Section: Landscape Genetics As An Approach To Understanding Pest Genementioning
confidence: 99%
“…The size of the experimental plots (landscapes) was selected based on previous studies of similar questions and organisms (Kareiva, 1987;Banks, 1999;Grez et al, 2004a, b;2005;Zaviezo et al, 2006). Previous theoretical and empirical studies suggest that fragmentation effects on population abundance and searching efficiency by natural enemies should be apparent only at high levels of habitat loss (i.e., over 70-80%, Andrén, 1994;Fahrig, 1997;With & King, 1999;Thies & Tscharntke, 1999;Flather & Bevers, 2002;With et al, 2002). Therefore, in our experiments we used percentages of habitat loss both above and below this threshold.…”
Section: Experimental Landscapesmentioning
confidence: 99%
“…It has been shown that those species belonging to higher trophic levels, such as parasitoids and predators, are more affected by habitat loss and fragmentation than are their prey, the herbivores (Hunter, 2002;Braschler et al, 2003;van Nouhuys, 2005;Ewers & Didham, 2006). Habitat fragmentation may adversely affect the ability of natural enemies to control pest outbreaks in agricultural landscapes by interfering with their searching behaviour and their aggregative numerical response to prey (Kareiva, 1987;With et al, 2002). Therefore, from the perspective of biological control, it is important to study whether changes in the agricultural landscape due to fragmentation and/or habitat loss, can affect the abundance of natural enemies, resulting in a failure to maintain pests at low populations levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation